(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article deals with the main model of the Ukrainian electricity market, its formation and dynamics. The organizational and economic directions of the electric power engineering processes from the point of view of implementation of investment and innovation support of the energy market of the region to the European standards are determined and a general assessment of the degree of transformation of the national energy sector to create a competitive and efficient market. The normative-legal support, foreign experience and formation of the domestic electricity market of Ukraine are considered, the European practice of effective mechanisms of state regulation is clarified, activity on the wholesale electricity market is analyzed, which is regulated by the Law of Ukraine "On Electricity" according to the "Single Buyer" Market Model, which will affect the solution of the problems of improving the national electricity sector. The peculiarities of the development of the world electricity market, indicators of the national electricity market, organizational and economic changes of the national electricity market are analyzed. The directions of improvement of the electric power market, based on the specification for each of the regional electricity markets of Ukraine, are proved. The strategic directions and risks in reforming the national electricity market are substantiated, directions of integration into the European space are determined. The forms and stages of organizational and economic directions in the national electricity market are outlined. The formation of the Ukrainian electricity market and the substantiation of organizational and economic changes in the energy sector to create a competitive and efficient national electricity market are considered. In order to achieve the intended purpose in the article the following tasks are set: to give a description of the electricity market of Ukraine; to investigate organizational and economic changes in the energy market; to consider the basic legal framework for the functioning of the national electricity market; to analyze the implementation of investment and innovation support of the energy market to European standards.